Design and in vitro evaluation of effervescent gastric floating drug delivery systems of propanolol HCl - Srikanth Meka, Venkata; Sunil Songa, Ambedkar; Rao Nali, Sreenivasa; Ram Battu, Janaki; Ramana Murthy Kolapalli, Venkata (Investigación Clínica, 2012)
The purpose of this research was to develop and evaluate effervescent gastric floating tablets of propranolol HCl. The oral delivery of antihypertensive propranolol HCl was facilitated by preparing an effervescent floating dosage form which could increase its absorption in the stomach by increasing the drug”™s gastric residence time. In the present work, effervescent floating tablets were prepared with a hydrophilic carrier such as polyethylene oxide (PEO WSR N 60K and PEO WSR 303) as a release retarding agent and sodium bicarbonate as a gas generating agent. The prepared tablets were evaluated for all their physicochemical properties, in vitro buoyancy, drug release and rate order kinetics. From the results, P9 was selected as an optimized formulation based on their 12 h drug release, minimal floating lag time and maximum total floating time. The optimized formulation followed first order rate kinetics with erosion mechanism. The optimized formulation was characterized with FTIR studies and no interaction between the drug and the polymers were observed.